FAKTOR BUDAYA YANG MEMPENGARUHI PERILAKU BERSIH DI PESANTREN : KAJIAN TERHADAP KULTUR PESANTREN YANG MEMPENGARUHI TINGKAT KESEHATAN SANTRI - Roikhatul Jannah Jannah (Poltekkes Kemenkes Jakarta III, 2016)
Islamic thought on cleanliness is well known with slogan cleanliness as part in believe. However, problem of cleanliness particularly gudig in a Pesantren has been being common among Indonesian. This means there is a gap between Islamic teaching, on cleanliness particularly hygiene thought, and its implementation among santri in Pesantren. This study explains why the gap exists in the pesantren. In 2009, the researcher observed two pesantrens in East and West Java; conducted FGD among santri, ustadz,and board of pesantren. The researcher also interviewed Kyai and his family member those play role as manager, leader as long as the owner of the pesantren. Indeed, this research data then updated in Muktamar NU 2015 in Jombang, west Java, along the discussion session about health status of Pesantren community, attended by santri, Kyai, pesantren board, member of a parliament member from health fraction, and health practitioners.data gathered then interpreted using ethnography perspective. The result showed that the gap between Islamic teaching about cleanliness and its implementation in the pesantren is affected from several reason as follow: (1) there are influences from Arabic culture imitated by pessantren community those were not always compatible with the Indonesian cultural environment; (2) pesantren community understands the thought in the context of ritual prayer;(3) the teaching methods in pesantren community contribute toward understanding santri about the meaning of the thought inproperly; (4) there is a culture in the pesantren, manifested in its apologetic language, to justify the problem of cleanliness without attempting to do anything.